ANALISA KELAYAKAN EKONOMI DAN FINANSIAL KERETA BANDAR UDARA RADEN INTEN II LAMPUNG - Dian Perwitasari; Ananda Agneshia Putri; Dicky Rahadianto (Jurnal Infrastruktur, 2021)
Lampung Province continues to experience increased population mobility and economic growth considering its location as the gateway to the island of Sumatra. The addition of transportation modes is a solution to the increasing need for comprehensive and optimal transportation. One of the efforts to increase the mode is the construction of a railway line to Raden Inten II Airport which is targeted to become an international airport. In this study, an analysis of the financial and economic feasibility of the railway line development was carried out with a quantitative approach using Life Cycle Costing (LCC) analysis. The calculations are made using several assumptions, including the increase in operating and maintenance costs, scenarios of passenger expectations and progress at each stage of construction, while the LCC analysis simulates the tariff price and year of concession. A project is declared economically and financially feasible by comparing the feasibility parameters such as NPV, BCR, IRR, and Payback Period. The results showed that in this optimistic scenario the airport train construction was declared economically and financially feasible.